TEACHER READINESS LEVEL FOR IMPLEMENTING THE "MERDEKA" CURRICULUM IN GRADE X OF BUILDING DESIGN AND INFORMATION MODELING CLASS AT SMK NEGERI 5 PADANG - Dewi, Melly Sentia; Andreas, Laras Oktavia (Jurnal Applied Science in Civil Engineering, 2023)
The "Merdeka" curriculum emphasizes aspects of student independence and courage in learning, as well as providing opportunities for teachers to develop teaching methods tailored to their students' needs. The purpose of this research is to determine the readiness level of teachers for implementing the "Merdeka" Curriculum in Grade X of Building Design and Information Modeling (DPIB) at SMK Negeri 5 Padang. This research used a quantitative descriptive method, with statistical analysis as the data analysis technique. A questionnaire with 19 statements was distributed to 14 respondents, including teachers teaching in the DPIB department and those teaching general subjects. After obtaining all the data, it was processed accordingly. The readiness level of teachers teaching in the DPIB department of Grade X at SMK Negeri 5 Padang falls into the "very ready" category. The readiness level of teachers for lesson planning is 85.35%, the readiness level for the "Merdeka" Curriculum in the learning process is 82.25%, both falling into the "very ready" category, and the readiness level of teachers for the implementation of the "Merdeka" Curriculum in the evaluation or assessment process is 85.43%, also falling into the "very ready" category.